Accounting for biodiverse wildlife corridor plantations. Issue 3 (17th September 2020) - Horner, Claire; Davidson, Neil
Abstract : Purpose: This paper aims to explore the feasibility of implementing the natural inventory model (NIM) developed by Jones (1996, 2003) in biodiverse wildlife corridor plantations, from a non-government organisations' (NGO) perspective. Design/methodology/approach: Undertaking the first cycle of an action research approach, the project involves collaboration with Greening Australia Tasmania (GAT). GAT is endeavouring to establish native wildlife corridors throughout the Tasmanian midlands, using science-based biodiverse plantations. The majority of the areas identified by GAT as essential for the establishment of these wildlife corridors are on privately owned land, primarily used for agricultural purposes. This paper explores whether stewardship of the land "sacrificed" by landowners may be demonstrated via the quantification and communication of improvements in biodiversity using the NIM. Findings: Results suggest that the existing NIM is impractical for use by an NGO with limited resources. However, with some adaptations incorporating science-based measurements, the NIM can be used to account for biodiverse wildlife corridor plantations. Practical implications: The findings have implications for not-for-profit, corporate and government sectors in terms of how accounting may facilitate the quantification and communication of conservation and restoration efforts. Social implications: Biodiversity loss is now considered to be a greater threat to the planet than climate change. Efforts to account for biodiversity are consistent with the UN 2030 Sustainable Development Agenda and the Australian Government's "Biodiversity Conservation Strategy" (2010). Originality/value: While prior studies have successfully implemented the NIM using secondary data, this is the first known to test the feasibility of the model using primary data in collaboration with an NGO.